Strategi Pengembangan Pariwisata Kota Pagar Alam - Hariani, Wita (Program Studi Administrasi Publik Universitas Muhamamdiyah Bengkulu, 2021)
Pagar Alam City is one of the tourist destinations in South Sumatra. Tourism objects, both natural attractions, religious tourism objects in general, still need more improvement and development. The tourism development strategy in Pagar Alam needs to be managed and considered better, namely by maximizing the need for development experienced by tourists and appropriate facilities and infrastructure. The mechanism that will determine how the service products provided by the government to tourists are in providing the best public services because the government's role is demanded for quality and has the ability to satisfy tourists. The purpose of this research, among others, is to know the Tourism Development Strategy of Pagar Alam City. In this study using descriptive type. Descriptive research is the steps to re-interpret objects about the state of social phenomena contained in the problems studied. The Government's steps in the Pagar Alam City Tourism Development Strategy are: (1) Tourism Object Facilities and Infrastructure Development Strategy, (2) Market Development Strategy, and (3) Human Resource Development Strategy